Late Mousterian and Aurignacian of Croatia: Environment, climate and chronology - Paunović, Maja (2003)
During the OIS stages 2 and 3 the northern Croatia was quite near to the ice cover of the Alps, i.e. part of the huge steppe area of the Pannonian basin. At the same time, Istria as well as the Adriatic coast was influenced both from the Mediterranean Sea and from the Alps, while the Dinarides played a role of a physiographic barrier between north and south. On the poster we present basic data for one site in North Croatia (Vindija: Mousterian, Early Upper Palaeolithic), and two localities at eastern Adriatic (Šandalja II: Aurignacian and Mujina Pećina: Mousterian). The late Mousterian assemblages from both regions are dated to approximately 45, 000 - 40, 000 years B.P., while the age of early Upper Paleolithic is estimated to be 33, 000 - 23, 000 years B.P. Typological analyses showed that there are differences between these two regions indicating cultural connections with Central Europe on the one side, and with Mediterranean regions on the other. It seems that Late Middle and early Upper Paleolithic people of Croatia have been successful hunters in different environments and that they have modified their technology to effectively exploit local raw materials and other natural resources for their subsistence.